"Conservación de canales de pollo con aplicación de bacterias ácido lácticas provenientes del mucilago de cacao (Theobroma cacao L.) - Castro Crespo, Alexa del Carmen (2019)
The present investigation was carried out in the Laboratory of Bromatology, located in the Experimental Farm "La María" of the State Technical University of Quevedo, located at km 7 ½ of the Quevedo - El Empalme road, San Felipe Campus; Canton Mocache, Province of Los Ríos. The same objective was to evaluate the effect of lactic acid bacteria as a preservative in the conservation of chicken carcasses in the Quevedo canton. The study was carried out with a completely random design in 3 x 3 factorial arrangement with 3 repetitions, as the first factor A: lactic acid bacteria extracted from the cocoa mucilage (National) and Factor B: time, resulting in 9 trématenos and 3 repetitions. The results obtained were analyzed in the statistical program Infostat, for the comparison of the means of the treatments a tukey test (p≤ 0.05) was used. which showed that there are significant differences, resulting that: 10% of cocoa mucilage reports the lower presence of E. coli and total coliforms, lower value in pH and temperature; At 6 hours there is a lower presence of E. coli and at 0 hours total coliforms, the lowest pH values are at 12 hours and temperature at 0 hours. The highest concentration of lactic acid bacteria was reported at 0 hours in 5, 10 and 15% of cocoa mucilage with 1.1 x 107 CFU and the lowest concentration was recorded at 12 hours in 15% of cocoa mucilage with 1, 6 x 105 CFU, so the hypothesis is accepted "The use of lactic acid bacteria increases the shelf life and decreases the degree of contamination of chicken meat." Key words: Mucilage, lactic acid bacteria, conservation, microbiological